A clinical tool to risk stratify potential kidney transplant recipients and predict severe adverse events. Issue 11 (18th October 2016) - Nygaard, Rachel M.; Sirany, Anne‐Marie; Wyman, Elizabeth A.; Bodner, Jennifer; Richardson, Chad J.; Ney, Arthur L.; Odland, Mark D.; Hill, Mark J.
Abstract: Preoperative risk assessment of potential kidney transplant recipients often fails to adequately balance risk related to underlying comorbidities with the beneficial impact of kidney transplantation. We sought to develop a simple scoring system based on factors known at the time of patient assessment for placement on the waitlist to predict likelihood of severe adverse events 1 year post‐transplant. The tool includes four components: age, cardiopulmonary factors, functional status, and metabolic factors. Pre‐transplant factors strongly associated with severe adverse events include diabetic (OR: 3.76, P <.001), coronary artery disease (OR: 3.45, P <.001), history of CABG/PCI (OR 3.1, P =.001), and peripheral vascular disease (OR 2.74, P =.008).The score was evaluated by calculation of concordance index. The C statistic of 0.74 for the risk stratification group was considered good discrimination in the validation cohort (N=127) compared to the development cohort (N=368). The pre‐transplant risk group was highly predictive of severe adverse events (OR 2.36, P <.001). Patients stratified into the above average‐risk group were four times more likely to experience severe adverse events compared to average‐risk patients, while patients in the high‐risk group were nearly 11 times more likely to experience severe adverse events. The pre‐transplant risk stratification tool is a simple scoring scheme using easily obtained preoperative characteristics that can meaningfully stratify patients in terms of post‐transplant risk and may ultimately guide patient selection and inform the counseling of potential kidney transplant recipients.